Decolonizing the Universal Child: A Critique of Hegemonic Rights Discourses in the Global South - Uche Nnawulezi; Jacques Kabano; Muhammad Iftar Aryaputra (Hukum dan Masyarakat Madani, 2026)
Children’s rights have gained universal recognition through various international human rights instruments, particularly the United Nations Convention on the Rights of the Child (UNCRC). However, prevailing discourses remain dominated by Western developmental paradigms and individualistic perspectives that are often criticized as forms of neo-colonialism for marginalizing the lived experiences, social relations, and cultural realities of children in the Global South. This article aims to examine how children’s rights can be decolonized by strengthening local contexts, to analyze how children in the Global South negotiate and interpret their rights, and to explore the contribution of local socio-cultural practices to the development of a decolonial perspective on children’s rights. This study employs a doctrinal legal research method based on the analysis of primary and secondary legal materials through conceptual and critical approaches. The findings reveal that the conception of children’s rights embodied in the UNCRC remains rooted in Western-centric epistemological assumptions, often overlooking the diversity of childhood experiences in the Global South. The study further demonstrates that children are active social agents who interpret and adapt their rights within specific social, economic, and cultural contexts. Local community practices, kinship relations, and informal social norms provide alternative conceptual frameworks that enrich understandings of children’s rights. The novelty of this article lies in integrating children’s agency, epistemic pluralism, and local knowledge systems as foundations for reconstructing a more inclusive and contextual children’s rights framework.   Abstrak Hak-hak anak telah memperoleh pengakuan universal melalui berbagai instrumen hak asasi manusia internasional, khususnya United Nations Convention on the Rights of the Child (UNCRC). Akan tetapi, diskursus yang berkembang masih didominasi oleh paradigma Barat dan pandangan individualistik yang kerap dipandang sebagai bentuk neo-kolonialisme karena memarginalkan pengalaman hidup, relasi sosial, dan realitas budaya anak-anak di Global South. Artikel ini bertujuan menganalisis bagaimana hak-hak anak dapat didekolonisasi melalui penguatan konteks lokal, mengkaji cara anak-anak di Global South menegosiasikan dan memaknai hak-hak mereka, serta mengeksplorasi kontribusi praktik sosial budaya lokal terhadap pengembangan perspektif dekolonial. Penelitian ini menggunakan metode doktrinal dengan menganalisis bahan hukum primer dan sekunder melalui pendekatan konseptual dan kritis. Hasil penelitian menunjukkan bahwa konsepsi hak-hak anak dalam UNCRC masih berakar pada asumsi epistemologis yang berpusat pada Barat sehingga sering kali mengabaikan keragaman pengalaman masa kanak-kanak di Global South. Temuan penelitian juga memperlihatkan bahwa anak-anak merupakan aktor sosial yang aktif dalam menafsirkan dan mengadaptasi hak-hak mereka sesuai konteks sosial, ekonomi, dan budaya setempat. Praktik komunitas lokal, relasi kekerabatan, dan norma sosial informal menyediakan alternatif konseptual yang memperkaya pemahaman mengenai hak-hak anak. Kebaruan artikel ini terletak pada pengintegrasian agensi anak, pluralisme epistemik, dan sistem pengetahuan lokal sebagai fondasi rekonstruksi kerangka hak anak yang lebih inklusif dan kontekstual.